Professional female athletes` adaptation specifics versus hormonal statuses - Pogodina, S. V.; Yuferev, V. S.; Aleksanyants, G. D. (Theory and Practice of Physical Culture, 2018)
The study analyzes the adaptation problems of 16-45 year-old professional female athletes versus their hormonal statuses. Research methods applied were as follows: immunological, biochemical, hematology tests, rheography, spyropneumotaxometry, gasometry and standard/ special load tests to rate the bodily system functionality and adaptability. In the competitive swimming group, the ovulation/ menstrual functionality was analyzed versus the bio-energy resource including the lactic acid generation in the anaerobic-aerobic and aerobic-anaerobic training regimen for the 16-36 and 37-45 year-old subgroups, respectively. The study data showed some age-specific differences in the non-specific adaptation processes - dominated by a smooth activation in the 37-45 year-olds versus some sagging of the activation threshold in the 16-36 year-olds in the first half (8-16 days) of the ovulation/ menstrual cycle. The 37-45 year-old non-ovulating/ menstrual subgroup, the 16-36 year-old ovulating/ menstrual subgroup and oral contraceptives applying subgroup were tested with some chronobiological variations of the hormonal and nervous-control effects on the cardiovascular and respiratory system adaptabilities. The ovulating/ menstrual and non-ovulating/ menstrual subgroups were tested with the highest hemodynamic and respiratory functionality rates in days 8-16 and 20-22 of the cycles, respectively. The oral contraceptives applying subgroup was tested with a notable stress of the key adaptation functions in days 8-16 of the menstrual cycle associated with the minimal estrogen levels.